A influência da amplificação sonora na queixa de zumbido de pacientes de um programa de saúde auditiva - Ferreira, Geise Corrêa (2017)
INTRODUCTION: With high prevalence among adults and the elderly people, tinnitus is commonly associated with hearing loss. One of the possibilities of intervention recommended in these cases is the use of hearing aids, as they can bring benefit to both complaints. Purposes: To investigate the influence of sound amplification on self-perception and the degree of discomfort of tinnitus in patients with hearing loss. Analyze and correlate the results obtained from the use of sound amplification, with the type of mold and acoustic modifications, or adaptation with thin tube, and the time of use of the hearing aids. METHODS: The sample group consisted of 32 patients aged between 22 and 86 years old, constant tinnitus complaints and hearing loss of different levels, with no prior experience with the use of sound amplification, starting the process of selection and adaptation of hearing aids. Before the adaptation of the hearing aids, the self-perception of tinnitus was investigated by means of a specific questionnaire to identify the situations and the frequency of their perception in the daily lives of the participants. The level of discomfort, in turn, was identified by means of note assignment on a numerical scale from 0 to 10. After 30 days of adaptation of hearing aids, with the effective use of at least six hours, the instruments were reapplied to obtain new parameters of the tinnitus complaint. After the completion of the second stage, we compared results obtained before and after the intervention and, then they were analyzed and compared to the resources used in the adaptation of the devices to verify the possibility of influence on tinnitus. RESULTS: In the pre-adaptation stage, tinnitus interference was observed in all daily activities in 12.5% of the participants; as well as the prevalence of self-perception in situations of silence, especially at night to sleep, and severe degree of discomfort. In the post-adaptation stage, a significant reduction was observed in all situations investigated in both the perception of tinnitus and the degree of discomfort. We found out that the degree of discomfort prevalent at this stage was mild, and 9 patients reported no more discomfort with tinnitus. In situations without the use of hearing aids, 6 patients reported no longer perceiving it, and the rest of the sample group mentioned the existence of perception mainly at night to sleep. There was a significant difference in the correlation between the results obtained from self-perception and discomfort with tinnitus. However, no significant correlation was observed between change of tinnitus with molds, ventilation or fine-tube adaptation, and the time of use of the devices. CONCLUSION: The use of sound amplification influenced the perception of tinnitus patients with hearing loss, providing reduction of self-perception and the degree of tinnitus discomfort, despite not having been found to influence the type of mold and acoustic modifications, as well as the time of hearing aids use.